Common Mistakes and Pitfalls in Magnetic Resonance Imaging of the Knee. Issue 1 (19th November 2016) - Vanhoenacker, Filip; De Vos, Nicolas; Van Dyck, Pieter
This pictorial review presents an overview of common interpretation errors and pitfalls in magnetic resonance imaging (MRI) of the knee. Instead of being exhaustive, we will emphasize those pitfalls that are most commonly encountered by young residents or less experienced radiologists.